решить представить в виде многочленов: 1) a(m+n)-b(m+n)=

2)5x(b-c)-(c-b)=

3)(x+3)(2y-1)-(x+3)(3y+2)

КапитанПрайс3000 КапитанПрайс3000    3   12.12.2020 11:37    0

Ответы
умка222 умка222  11.01.2021 11:38

1) a(m+n)-b(m+n)= am+an-bm-bn

2)5x(b-c)-(c-b)= 5bx-5cx-c+b

3)(x+3)(2y-1)-(x+3)(3y+2)= -xy-3x-3y-9

ПОКАЗАТЬ ОТВЕТЫ
topwkolnik topwkolnik  11.01.2021 11:38

a(m+n)-b(m+n)= am+an-bm-bn

2)5x(b-c)-(c-b)= 5bx-5cx-c+b

3)(x+3)(2y-1)-(x+3)(3y+2)= -xy-3x-3y-9

Объяснение:

a(m+n)-b(m+n)= am+an-bm-bn

2)5x(b-c)-(c-b)= 5bx-5cx-c+b

3)(x+3)(2y-1)-(x+3)(3y+2)= -xy-3x-3y-9

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра